Effect of cavity disinfection protocols on microtensile bond strength of universal adhesive to dentin = Efecto de los protocolos de desinfección de cavidades en la fuerza de adhesión microtensil del adhesivo universal a la dentina - Bilgili Can, Dilber
The purpose of this study was to compare the effect of different disinfection protocols of dentin on bond strength of an MDP-containing universal adhesive. Twelve extracted mandibular third molars were separated horizontally at the mid-coronal of crown to get smooth and sound dentin surfaces using low-speed diamond saw. The teeth were randomly fallen into four groups: chlorhexidine (CHX), ozone, Er,Cr:YSGG laser irradiation (LASER) and no treatment (control). After cavity disinfection application, a universal adhesive (G-Premio Bond) was applied to the surface of dentin according to self-etch mode as instructed by the manufacturer. After incremental built-up of composite resin (Charisma Smart), the specimens were immersed in distilled water at 37°C for 24h. Dentin/composite beams with 1 mm² cross sectional area were produced and micro-tensile bond strength (μTBS) was applied on these beams (n=20). Failure mods were determined under a stereomicroscope at ×40. The resin penetration of samples stained with Rhodamine B fluorochrome dye was examined with a confocal laser scanning microscope. Statistical analysis was performed with SPSS-22. Test results were analyzed using One-way Anova and Tukey HSD Post-Hoc tests (p<0.05). The μTBS value of control (35.13±6.20) was the highest statistically among the groups (p<0.05). The lowest μTBS were obtained by LASER (19.25±4.66) and CHX (23.07±7.01). There was no significant difference between CHX and LASER, and between CHX and ozone (p>0.5). All applications of cavity disinfection procedures decreased the μTBS of the resin-dentin interface.